Linguistic and Cultural Studies: The Quest for New Ideas - Kononenko, Vitalii (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article highlights the principles of researching into text from the interdisciplinary linguistic and cultural perspective. Cognitological analysis of linguistic and extralinguistic cultural meanings reveals that there exist of specific linguistic and aesthetic formations best presented through the ‘language – culture – identity’ triad. One of the components of literary discourse is monocultural layer, which secures the continuity of national cultural tradition; researching into it, one should take into account mental and historical, psycholinguistic, sociolinguistic and other factors. Linguistic and aesthetic analysis helps to establish the system of linguistic and cultural means (metaphorization, imagery, verbal symbols, linguistic conceptualization, connotative meanings), which reveals its potential in literary texts. The lingual identity as a general notional category shows its nationally-oriented characteristics through the dichotomies of ‘addresseraddressee’ , ‘author-reader’, ‘narrator-narratee’ and is presented in the author’s idiolect